A-Kinase-Anchoring Protein (AKAP150) is expressed in Astrocytes and Upregulated in Response to Ischemia. (1st August 2018) - Rivera-Pagán, Aixa F.; Méndez-González, Miguel P.; Rivera-Aponte, David E.; Malpica-Nieves, Christian J.; Melnik-Martínez, Katya V.; Zayas-Santiago, Astrid; Maldonado-Martínez, Gerónimo; Shuba, Yaroslav M.; Skatchkov, Serguei N.; Eaton, Misty J.
Highlights: The present study confirms that AKAP150 is present in astrocytes. Moreover, AKAP150 in astrocytes is up-regulated during ischemia. AKAP150 modulates the astrocytic membrane potential during ischemic conditions. Knock-down of AKAP150 decreases the ability of astrocytes to buffer extracellular potassium during ischemic conditions. Abstract: A-kinase-anchoring proteins, AKAPs, are scaffolding proteins that associate with kinases and phosphatases, and direct them to a specific submembrane site to coordinate signaling events. AKAP150, a rodent ortholog of human AKAP79, has been extensively studied in neurons, but very little is known about the localization and function of AKAP150 in astrocytes, the major cell type in brain. Thus, in this study, we assessed the localization of AKAP150 in astrocytes and elucidated its role during physiological and ischemic conditions. Herein, we demonstrate that AKAP150 is localized in astrocytes and is up-regulated during ischemia both in vitro and in vivo . Knock-down of AKAP150 by RNAi depolarizes the astrocytic membrane potential and substantially reduces by 80% the ability of astrocytes to take up extracellular potassium during ischemic conditions. Therefore, upregulation of AKAP150 during ischemia preserves potassium conductance and the associated hyperpolarized membrane potential of astrocytes; properties of astrocytes needed to maintain extracellular brain homeostasis. Taken together, these data suggest that AKAP150 may play a pivotal role in the neuroprotective mechanism of astrocytes during pathological conditions.